Modifying the Regulations in Geudeu-Geudeu Martial Art - Nyak Amir; Saifuddin Saifuddin; Riyan Maulana (Proceedings of AICS - Social Sciences, 2021)
The Acehnese in Indonesia from Pidie district are fond and proud of their traditional sport or martial art called Geudeu-geudeu. Thus, there are some concerns by these Acehnese to perform the martial art in competitions since there are dangerous moves that do not have clear regulations on their conducts. Based on this problem, this study proposes some modifications on the regulations in performing Geudeu-geudeu. This is deemed important to encourage the people to perform and preserve this traditional sport. A number of ten Geudeu-geudeu coaches were interviewed to collect data. The results of the interviews revealed that there are 11 indicators and 92 items from the modification variables of Geudeu-geudeu regulations which include the game field, rounds, players and weight of players, age, equipment, form of moves, general rules, restrictions, scoring, violations, penalty, jury, referee and judge. Regarding the modification of Geudeu-geudeu regulations, 62.23% of the participants strongly agreed to it, 34.24% chose to agree, 3.26% chose to disagree and 0.27% strongly disagreed. Hence, it can be concluded that more than half of the participants support the modification of Geudue-Geudeu regulations to make this traditional sport more accessible and maintained by the Acehnese by performing them in competitions or traditional ceremonies.Keywords: modification, regulations, geudeu-geudeu, martial art, traditional sport.